Significant Removal of Harmful Compounds in Mainstream Cigarette Smoke Using Carbon Nanotubes Mixture Prepared by Catalytic Pyrolysis - Shun Zhou; Min Ning; Yaping Zhang; Qing He; Xiaofeng Wang; Dongliang Zhu; Song Guo; Ningning Hong; Yuan Hu (Adsorption Science & Technology)
Carbon nanotubes mixture (CNTM), synthesized by the pyrolysis of polypropylene (PP)/organically modified montmorillonite (OMMT) nanocomposites catalyzed by Ni2O3, was used as a filter additive to remove harmful compounds in mainstream cigarette smoke. CNTM is mainly composed of carbon nanotubes (CNTs) with a little amount of amorphous carbon, Ni element and the thermal degradation residue of OMMT. The textural structure of CNTM has mesoporous and macroporous nanostructures. After introducing 15 mg of CNTM into cigarette filter, some of the most important harmful compounds including tar, nicotine, benzo[a]pyrene (B[a]P) and phenolic compounds were more efficiently adsorbed in comparison with using commercial activated carbon, which can be related to the relatively bigger pore volume and a geometric confinement of CNT in CNTM for some toxic compounds in cigarette smoke. In particular, CNTs have a strong chemisorption capacity for B[a]P or phenolic compounds due to the π–π interactions between benzene rings.